1998
DOI: 10.1038/sj.bmt.1701133
|View full text |Cite
|
Sign up to set email alerts
|

CD34+ cells mobilized by cyclophosphamide and granulocyte colony-stimulating factor (G-CSF) are functionally different from CD34+ cells mobilized by G-CSF

Abstract: Summary:Mobilized peripheral blood progenitor cells (PBPC) are increasingly used as an alternative to bone marrow for autografting procedures. Currently, cyclophosphamide (CY) followed by granulocyte colony-stimulating factor (G-CSF) or G-CSF alone are the most commonly used PBPC mobilization schedules. In an attempt to investigate whether the use of these two mobilization regimens could result in the collection of functionally different CD34 ؉ cells, we analyzed nucleated cells (NC), CD34 ؉ cells, committed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
0
19
1
1
Order By: Relevance
“…Median time to reach a platelet count420 Â 10 9 /l was 12.2 days (range [10][11][12][13][14] in the 'G-CSF alone' mobilized group and 14.5 (range 11-23) days in the 'cyclophosphamide plus G-CSF' mobilized group (log-rank test: P-value ¼ 0.33).…”
Section: Transplantation Results In Successfully Mobilized Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Median time to reach a platelet count420 Â 10 9 /l was 12.2 days (range [10][11][12][13][14] in the 'G-CSF alone' mobilized group and 14.5 (range 11-23) days in the 'cyclophosphamide plus G-CSF' mobilized group (log-rank test: P-value ¼ 0.33).…”
Section: Transplantation Results In Successfully Mobilized Patientsmentioning
confidence: 99%
“…In fact, in two studies, the amount of CD34+ cells harvested after these two regimens was similar, 12,13 while other authors found a higher mobilizing capacity for the association 'cyclophosphamide plus G-CSF'. [14][15][16] Furthermore, when studied as second line mobilization therapy in patient failing a previous mobilization scheme, 'G-CSF alone' and 'cyclophosphamide plus G-CSF' have been considered of equivalent efficacy.…”
Section: Mobilization; Cd34+ Cellsmentioning
confidence: 94%
“…[6][7][8][9][10] Some studies have shown a higher yield of CD34 þ cells following chemotherapy and growth factors than growth factors alone. 2,6 Although increasing the cyclophosphamide dose in combination with growth factor produces increased numbers of CD34 þ cells, this is associated with increased toxicity and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…6 Some studies have demonstrated the yield of CD34 þ cells to be superior to in-patients who have been treated with chemotherapy and growth factors rather than growth factor alone. 6,9,10 There has been only one previous randomised study comparing cyclophosphamide and G-CSF with G-CSF alone. 1 In this trial, we investigated the yield of CD34 þ cells following intermediate dose of cyclophosphamide followed by lenograstim (Cyclo-G-CSF group) vs lenograstim alone at 10 mg/kg/day (G-CSF group).…”
mentioning
confidence: 99%
See 1 more Smart Citation